2021
DOI: 10.3390/su13105363
|View full text |Cite
|
Sign up to set email alerts
|

Manure Flushing vs. Scraping in Dairy Freestall Lanes Reduces Gaseous Emissions

Abstract: The objective of the present study was to mitigate ammonia (NH3), greenhouse gases (GHGs), and other air pollutants from lactating dairy cattle waste using different freestall management techniques. For the present study, cows were housed in an environmental chamber from which waste was removed by either flushing or scraping at two different frequencies. The four treatments used were (1) flushing three times a day (F3), (2) flushing six times a day (F6), (3) scraping three times a day (S3), and (4) scraping si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Steers fed RAC vs. control rations showed lower NH 3 emission by 17.21% from d 0 to 28 (p = 0.032) and a trend for lower emissions from d 0 to 42 by 11.07% (p = 0.070). Ractopamine simultaneously increased beef cattle performance reduced NH 3 emissions [100].…”
Section: Feeding Management-diet Manipulation: Cp and Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…Steers fed RAC vs. control rations showed lower NH 3 emission by 17.21% from d 0 to 28 (p = 0.032) and a trend for lower emissions from d 0 to 42 by 11.07% (p = 0.070). Ractopamine simultaneously increased beef cattle performance reduced NH 3 emissions [100].…”
Section: Feeding Management-diet Manipulation: Cp and Ctmentioning
confidence: 99%
“…β-AA promotes protein synthesis in livestock, reducing N excretion. The reduced N excretion mitigated NH 3 emission (11 to 17%) from β-AA feeding [100]. Ross [100] conducted an experiment to determine the efficacy of feeding ractopamine hydrochloride (RAC) for the last 42 days of the finishing period to reduce NH 3 emissions and improve animal performance.…”
Section: Feeding Management-diet Manipulation: Cp and Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination significantly enhances manure management, a key factor in the generation of methane and ammonia emissions [40]. The effectiveness of these systems lies in their ability to rapidly remove manure, thus limiting its exposure to air and significantly cutting down on the emission of noxious gases [41,42]. The reduction in ammonia volatilization is particularly notable, as the frequent removal of manure inhibits the enzymatic processes crucial for the transformation of urea in manure into ammonia.…”
Section: Low-emission Floors With Slurry Scrapersmentioning
confidence: 99%
“…The researchers opined that future work should focus on understanding the effects of long-term supplementation or high dose of 'SOP STAR COW' to regulate mitigation effects on methane emissions and increase in milk production can be ascertained. In another report, Ross et al [9], by adopting various free-stall management techniques studied the means to lessen ammonia, greenhouse gas, and some air pollutants from lactating dairy cattle wastes. From the study, it was concluded that removal of dairy manure by 'scraping' holds a high prospective to enhance gaseous emissions such as ammonia and other greenhouse gases.…”
mentioning
confidence: 99%